Cartilage Tissue Engineering: Investigation of Migration and Differentiation of Human Mesenchymal Stem Cells on Five‐Layered Collagenous Electrospun Scaffold Mimicking Native Cartilage Structure (Adv. Healthcare Mater. 17/2016). Issue 17 (September 2016) - Reboredo, Jenny W.; Weigel, Tobias; Steinert, Andre; Rackwitz, Lars; Rudert, Maximilian; Walles, Heike
Abstract : On page 2191, the preparation of a multilayered electrospun scaffold that has the potency to induce chondrogenic differentiation of human mesenchymal stem cells in vitro is reported by Jenny W. Reboredo and co‐workers. The novel biomaterial consists of collagen type I and II and is designed for the replacement of damaged cartilage that allows repopulation by host cells and synthesis of a new natural matrix.